(untitled) - HARIYANI, LISA (LATERNE, 2013)
The error analysis is is a procedure commonly used work by writers and language teachers, through collecting data, identification of errors contained in the data, explanation of the error, error classification based on the cause, and evaluation or assessment of the level of seriousness of error. Writing means as an activity to express idea by using the language of writing as a media to transfer.The problem of this research ist what kind of writing error that made by the students of class XI IPA 1 SMA Negeri 1 Gedangan in a German essay? The aims of this research ist looking for any writing errors made ??by the students of class XI IPA 1 SMAN 1 Gedangan in Germany essay. The method of this research is descriptive qualitative. After the author analyzed the datas, it could conclude that many of the errors found in the field of conjugation, sentence structure, declination and orthography. Based on the results of this study suggested that with this study can be used as material to find the right method in improving students’ Schreibfähigkeitens, especially in making a simple essay with good and correct grammar structures. So in the future students do not make the same mistake over and over again. Keywords : The error analysis, Schreibfähigkeitens, Germany essay.